Security issues and Challenges in MANET-VANET-FANET: A Survey - Ahmed Sumra, Irshad; Sellappan, P.; Abdullah, Azween; Ali, Ahmad (EAI Endorsed Transactions on Energy Web, 2018)
Security is one of the key important factors in ad hoc network due to the open wireless medium and dynamic topology of the network. MANET, VANET and FANET are type of ad hoc network and their applications are served the end users in real environment. VANET and FANET are next generation network and due to safety applications more attractions for end users in these networks. In this paper, we will provide the survey on security issues and challenges in the field of MANET, VANET and FANET. The successful implementation of these networks in real environment, it is require the network will be secure and end user can take benefit from their life safety applications.